Resource Empowerment and Optimization of Beach Tourism Facilities in Delegan, Gresik, East Java - Mahmud Mustain; Sujantoko; Anggita Deva Ariyanti (International Journal of Offshore and Coastal Engineering, 2025)
The discipline of Integrated Coastal Zone Management (ICZM) is still growing, especially in Indonesia, but its implementation is still relatively young. This study focuses on beach tourism. Ecotourism development and management is one of the efforts to utilize local resources that must be optimal. Delegan Gresik Tourism Beach, East Java, is a management research area for ecotourism development. This research aims to determine the potential of existing resources in Delegan Beach attractions and make scenarios for development plan efforts. This is done through Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis and interviews to determine resource potential, development alternatives and priorities, both through analysis of internal and external factors. The results of this study show that forms of stakeholder participation influence the determinants of the development of natural tourism areas on Delegan Beach. The resulting development directions include the use of various resources, the development of facilities as community business opportunities, the empowerment of community skills, the Improvement of regional socialization, and efforts to preserve the environment.